Performance study of an absorption cooling system under different energy sources - Tang, Chung Hieng. (Universiti Malaysia Sarawak (UNIMAS), 2010)
In the present study, a H20-NH3-H2 ccoling machine, which used ammonia (NH3) as refrigerant, water as adsorbent and hydrogen as equalizer for pressure, has been employed and investigated. The first objective of this work is to assess the transient temperature of the system's components under the two types of energy sources: Electric grid and Liquid Petroleum Gas which can be easily obtained and integrated to the absorption refrigeration for residential usage. Five sets of experiments were done under the lab enviroment at 27C. In the experiments, the data was recorded every minute within two hours. Five sets of data were collected and analyzed with statiscal analyses.